The level of digitization of small, medium and large enterprises in the Central and Eastern European countries and its relationship with economic parameters - Jarosław Brodny; Magdalena Tutak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Dynamic changes in the global economy, resulting from the implementation of the Industry 4.0 concept, cover practically all areas of life. They mainly concern companies that need to adapt to these changes as soon as possible in order to face growing competition. The digitalization process is of great significance in this respect, as it requires having appropriate material and personal resources as well as knowledge necessary to implement new innovative solutions. Problems associated with the digitalization of economy are very well understood in the European Union (EU), which makes every effort to ensure the best possible conditions for the implementation of this process in companies in all member states. A special group of these countries belong to Central and Eastern Europe (CEE), the youngest members of the EU. Given this extremely important issue, the paper presents the results of research on the level of digitalization of small, medium and large enterprises in this group of countries (CEE). Their aim was to evaluate the level of digitalization of the studied groups of enterprises and individual CEE countries. It was important to determine digital technologies dominating in particular groups of enterprises and, with the use of non-parametric tests, the influence of the digitalization level on selected economic parameters of particular CEE countries. The research was based on 11 selected indicators characterizing the digital technologies used, infrastructure for Industry 4.0 and personnel training in new technologies. The level of digitalization of individual groups of companies was determined based on the multi-criteria decision-making method (MCDM). In this case, the TOPSIS and VIKOR methods were applied, for which the rankings and levels of digitalization of individual CEE countries were also determined. The entropy and CRITIC methods were utilized to measure the weights of indicators adopted for the study. The whole research was complemented by statistical analyses of the adopted indicators. The results showed a high differentiation in the level of digitalization for individual CEE countries and the studied groups of enterprises. The highest levels of digitalization were reported in Slovenia, Croatia and the Czech Republic. The lowest levels were reported in Bulgaria and Romania. From the point of view of the size of enterprises, the highest levels of digitalization were found in the group of large enterprises, which results from their potential and resources. The results are an important source of information regarding the current state of digitalization in the CEE countries, considering the size of enterprises. This, in turn, should be used when developing strategies for the digital transformation of the CEE countries and the entire EU.
Keywords: 650; CEE countries; digitalization; hybrid MCDM approach; Industry 4.0; medium and large enterprises; open innovation; small